Pengaruh Aksesibilitas dan Fasilitas terhadap Kepuasan Konsumen Halsean Coffee & Resto - Valerina R., Muthia; Adysholihah F., Rina (Asosiasi Ahli Administrasi Indonesia, 2022)
Currently, enjoying coffee has become a lifestyle for the community, this makes coffee shops one of the promising businesses in Indonesia. But it is undeniable, business people must pay attention to supporting factors such as access, facilities and other factors in building a coffee shop. Therefore, this study was made with the aim of examining the effect of accessibility, facilities, and customer satisfaction at Halsean Coffee & Resto. This study uses an explanatory method with a quantitative approach. A total of 300 visitors to Halsean Coffee & Resto in Cimahi and surrounding areas were involved in this research. Data analysis in this study used frequency analysis, factor analysis, data normality analysis, and simple regression analysis with the help of SPSS v.24 software. The results of data analysis found that accessibility has a negative and insignificant direction on customer satisfaction, on the contrary, facilities have a positive and significant direction on customer satisfaction.